Al-Shafiis Writings on Hadith - Ali, Abdul Karim (Jurnal Usuluddin, 1997)
This article attempts to discuss al-Shafiis writing on hadith. His writings could be divided into two categories. First, his writings on the importance ofhadith, khabar al-wahid and others. Second, his collection of hadiths.This article is also to analyse the significance of these writings to Islamic jurisprudence.